Pengembangan Media SH POP untuk Meningkatkan Literasi Baca Tulis Siswa Sekolah Dasar - Winarni Winarni (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
This study aims to test the feasibility of SH POP media in improving the literacy skills of elementary school students. This type of research is development research referring to the opinion of Borg & Gall. The design of the development of this learning device includes 10 steps, namely (1) preliminary research and information collection; (2) planning; (3) product draft development; (4) initial trial; (5) revise the results of the limited trial; (6) field trials; (7) refinement of the product from field trials; (8) operational field trials; (9) final product refinement, and (10) dissemination. The research subjects were students of class IIID SDIT Izzatul Islam Getasan Kab. Semarang. Data collection techniques used are questionnaires and tests. The data analysis technique uses Miles & Hubberman interactive analysis. The results showed that the feasibility of the SH POP media showed a validity score of 91, a practicality score of 91, and an effectiveness score of 86. This proves that the SH POP media is feasible to improve the literacy skills of elementary school students.